Exports, Terms of Trade and Economic Growth: Evidence from Countries with Different Level of Openness - Dabús, Carlos Darío (2019)
This paper explores the effects of the ratio exports/GDP and the terms of trade on growth among countries with different level of development and openness. These effects vary among subgroups of countries with different openness and per development level. Nonetheless, in general the evidence seems to support the hypothesis stated in this research. In less developed or better endowed for export countries one or both of the explanatory variables mentioned above encourage for economic growth. Specifically, in advanced economies only the ratio exports/GDP is growth promoting when these are open, and have high per capita but small global GDP and/or relative advantages to be growth export-led. In turn, exports or and the terms of trade trends to promote growth in lower middle income countries. Unfortunately, the surprising results came from the poorest countries. They do not are benefited from a more favourable foreign environment. On the contrary, exports are not significant while an improvement in the terms of trade diminishes their growth.